(untitled) (Acta Scientiarum. Health Sciences, 2022)
The existence of an association between negative attitudes from health professionals, such as prejudice, stigma and discrimination, can lead to difficulties in dealing with a person who has attempted suicide and, consequently, to a decrease in the quality of the care provided. In this context, this article aimed to verify attitudes related to suicidal behavior among nursing students at a private educational institution in the Federal District, Brazil. It was a quantitative, descriptive study that used two questionnaires: a sociodemographic and academic one, and another with questions addressing attitudes towards suicide, called Questionnaire on Attitudes Towards Suicidal Behavior. A total of 253 nursing students participated; in general, the data revealed that they did not have any negative attitude towards suicidal people. The main attitudes that brought some difficulty to students were related to: asking about suicidal behavior and inducing someone to go ahead with it; feeling helpless when faced with a person who thinks about killing themself; lack of professional preparation to deal with patients who have gone through this psychological suffering of attempting self-extermination; and the presence of a conservative and religious attitude towards suicide. Understanding the attitudes of students in the health field, especially nursing students, still in the training period, can bring about a change in the understanding of suicidal behavior, a prejudice-free nursing care, strengthen broad discussions around the topic, openly and without taboos, as well as provide a comprehensive and humanized care.